Kaposi sarcoma-associated herpesvirus/human herpesvirus 8 and lymphoproliferative disorders. Issue 12 (27th November 2007) - Du, M-Q; Bacon, C M; Isaacson, P G
Abstract : Kaposi sarcoma-associated herpesvirus (KSHV), also known as human herpesvirus 8 (HHV8), is a recent addition to the list of human viruses that are directly associated with lymphoproliferative disorders. KSHV was first shown to be involved in multicentric Castleman disease and primary effusion lymphoma (PEL). Subsequently, the virus was identified in solid lymphomas, often of extranodal sites, with morphological and immunophenotypic characteristics similar to those of PEL, and in other lymphoproliferative disorders with heterogeneous clinicopathological presentations. The recent advances in our understanding of the histology, immunophenotype and pathogenesis of these KSHV-associated lymphoproliferative disorders are reviewed.